1887 Wis. Sess. Laws 754, ch. 162, § 3, pt. 36 - (:unkn) unknown (General Publisher, 1887)
Authorized the city to regulate and prohibit the concealed carry of any pistol, slung shot, knuckles, bowie knife, dirk, or any other dangerous or deadly weapon.
--
Keywords: CARRY - CONCEALED